2020
DOI: 10.3390/min10030251
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Operating Parameters on Dry Grinding of Calcite in a Stirred Media Mill Using the Box-Behnken Design

Abstract: The optimization of the operating parameters of a stirred media mill in the dry grinding of calcite was investigated. A three-level Box-Behnken design was used for the purpose of examining the impact of four independent factors, the stirrer speed (SS), grinding time (GT), media filling ratio (MFR), and solid mass fraction (SMF), on the product particle size (d50). For the purpose of establishing an empirical correlation between operating parameters and responses, a series of experiments were carried out. Varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…For the achievement of SDGs, the improvement of energy consumption in the dry grinding processes is significantly important. Many researches relating to the analysis of energy consumption discuss the energy efficiency using the specific grinding energy and/or electric power consumption (Altun et al, 2015;Altun et al, 2019;Blanc et al, 2020;Katircioglu-Bayel et al, 2020;Ngamnikom and Songsermpong, 2011;Ogonowski et al, 2018;Tamura et al, 2017;2020). In particular, Prziwara, Kwade and co-workers (Prziwara et al, 2018a;2018b;2018c;2020a) have actively studied in detail the effects of grinding aids on the grinding efficiency in dry fine grinding processes.…”
Section: Possible Contribution Of Dry Grinding To Sdgsmentioning
confidence: 99%
“…For the achievement of SDGs, the improvement of energy consumption in the dry grinding processes is significantly important. Many researches relating to the analysis of energy consumption discuss the energy efficiency using the specific grinding energy and/or electric power consumption (Altun et al, 2015;Altun et al, 2019;Blanc et al, 2020;Katircioglu-Bayel et al, 2020;Ngamnikom and Songsermpong, 2011;Ogonowski et al, 2018;Tamura et al, 2017;2020). In particular, Prziwara, Kwade and co-workers (Prziwara et al, 2018a;2018b;2018c;2020a) have actively studied in detail the effects of grinding aids on the grinding efficiency in dry fine grinding processes.…”
Section: Possible Contribution Of Dry Grinding To Sdgsmentioning
confidence: 99%
“…It was observed that the stirrer speed (D), temperature (A), and digestion time (B) had positive effects, meaning an increase in these main factors would increase the W recovery. The stirrer speed had the largest contribution of 58.5% because it relates to the particle size reduction, increases the surface area, and enhances the reactivity of scheelite [10,23]. It also enhances mass transfer in the highly viscous NaOH digestion solution and continuously removes the Ca(OH) 2 solid product layers that form on scheelite mineral particles as the accelerated rate-determining chemical reaction (Equation 1 Despite temperature and digestion time individually having a positive effect on W recovery, their interactions (AB) showed a negative effect, and this contribution was larger than that of the individual factors.…”
Section: Leaching Proceduresmentioning
confidence: 99%
“…Reducing both the stirrer speed and the digestion time to have a high leaching temperature had a more negative effect on W recovery because the mechanical activation of scheelite was reduced. With the coarser tailings used in this study, particle size reduction, which is essential for increased scheelite reactivity [10,23], is less enhanced.…”
Section: Optimizationmentioning
confidence: 99%
See 2 more Smart Citations